A decentralized DSO-MGOs coordination approach for TSO-DSOs coordination and security enhancement - Meethaq Talib Jabbar Alramahy; Sajjad Golshannavaz; Vahid Talavat (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The distribution system operator (DSO) plays a vital role in effective distribution of energy among diverse consumers and energy exchanges between microgrids (MGs). On the higher levels and within the emergent of smart grid paradigms, the interactions between the DSO and the transmission system operator (TSO) also seems essential for achieving an optimal power flow (OPF) within the transmission systems alongside contemplating security amendments. This paper models an advanced energy management technique considering decentralized peer-to-peer (P2P) collaborations on the demand side, highlighting how enhanced cooperation between DSOs and MG operators (MGOs) can reinforce the connection with the TSO. Moreover, the main focus is on security-constrained optimal power flow (SCOPF) and its enhanced indicators ending to the overall power system security enhancement. To do so, this research models a transmission network operation framework that incorporates remarkable set of distributed energy resources (DERs), organized by multiple distribution systems, each hosting several MGs including end-use consumers. The proposed approach models energy interaction among smart homes considering smart appliances and small-scale DERs. The results show a positive impact on reducing load profile deviations of each distribution system. Also, it reduces the operating cost of the transmission system by 9.8% and improves the security margin by 33.9%, which is a remarkable performance.